Determination of energy storage capacity requirement for large wind farm or photovoltaic system - Chan, Sin Chuen. (2009)
This report serves the purpose of proposing methodologies to determine the energy storage capacity of large photovoltaic (PV) system. Due to the natural weather/climatic conditions, the solar radiation level is intermittent and it cannot able to be predicted with high precision. This means that the power output from the PV system is rather unsteady. In addition, the solar energy distribution does not coincident perfectly with the electric load profile. This could result in undesirable disruption of power supplied by the PV system especially during low sunshine periods. Integrating the PV system with energy storage systems is a possible solution. The energy storage system will be charged when the PV output is higher than the required load demand, and it will be discharged when there is little or no sunshine.